Urgentna medicina (University of Maribor Press, 2022)
Emergency Medicine. The textbook Emergency Medicine is the first university textbook in the field of emergency medicine published in the Slovenian language and is divided into three parts. The first part contains a description of the organisational structure of Emergency Medical Services in Slovenia as well as the fundamentals of emergency medicine. The second and third parts cover the essentials of accidents and emergencies. The textbook presents the most common emergencies encountered in emergency medicine and follows the recommendations of the European Society for Emergency Medicine. Individual contributions are designed in such a way that the pathophysiology is presented first, followed by the clinical features, diagnosis, management and treatment. Special emphasis was placed on clinical approach. This book is intended for undergraduate medical students and medical interns preparing for the professional examination. The textbook will also be a useful tool for physicians of other medical specialties working in emergency medical care. 7. 5. 2025 Third reprint of first edition 20. 11. 2023 Second reprint of first edition 7. 3. 2023 First reprint of first edition